2023
DOI: 10.1088/1741-2552/ac8bfd
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial ultrasound stimulation relieves depression in mice with chronic restraint stress

Abstract: Objective: Exhaustion of Serotonin (5-hydroxytryptamine, 5-HT) is a typical cause of the depression disorder’s development and progression, including depression-like behaviors. Transcranial ultrasound stimulation (TUS) is an emerging non-invasive neuromodulation technique treating various neurodegenerative diseases. This study aims to investigate whether TUS ameliorates depression-like behaviors by restoring 5-HT levels. Methods: The depression model mice are established by chronic restraint stress (CRS). Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…Tryptophan is the sole precursor of 5-HT, which is an important monoamine neurotransmitter. Many studies have reported that the level of 5-HT was significantly decreased in depression Zhu et al, 2022). Our previous studies also found the significantly decreased level of 5-HT in depression patients' plasma and brain areas of depressed mice (Wu et al, 2020;Tian et al, 2022;Xie et al, 2023).…”
Section: B a Figuresupporting
confidence: 55%
“…Tryptophan is the sole precursor of 5-HT, which is an important monoamine neurotransmitter. Many studies have reported that the level of 5-HT was significantly decreased in depression Zhu et al, 2022). Our previous studies also found the significantly decreased level of 5-HT in depression patients' plasma and brain areas of depressed mice (Wu et al, 2020;Tian et al, 2022;Xie et al, 2023).…”
Section: B a Figuresupporting
confidence: 55%
“…However, the maximum ultrasound pressure of the transducer is only 300 kPa, which is difficulty to open the BBB. The ultrasound pressure required for some ultrasound neuromodulation experiments is more than 300 kPa [57,58], which is difficult to meet. The system developed in this study can achieve a maximum ultrasound pressure of 1.8 MPa while generating bifocal ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the supernatant was filtered by using a filter membrane, and the filtrate was used for assays. LC and MC analysis conditions are the same as those described in our previous work [13].…”
Section: Lc-ms Analysismentioning
confidence: 99%
“…However, acute optogenetic activation of the DRN increased active stress-coping in rats and mice, and long-term activation of serotonergic neurons might produce a long-term positive stress response [19]. Our prior study indicated that TUS of DRN could improve the depression-like behaviors in depression mice models [13], which suggests that DRN may be one of the effective targets of TUS in treating depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation